Self-Discovery and Individuation Process in Matt Haig’s The Midnight Library - Daimatus Sholikhah; Anita Rahmah Dewi (FKIP, Universitas Billfath Lamongan, 2025)
This research aims to analyze the process of self-discovery and individuation of the main character in Matt Haig's novel